THE CONCEPT OF PAUD EDUCATION IN THE FAMILY ENVIRONMENT ACCORDING TO ISLAMIC EDUCATION - Ahmad Rifai; Husin; Fatimah; Abdul Rashid bin Abdul Aziz (International Forum of Researchers and Lecturers, 2022)
Early Childhood Education (PAUD) is a coaching effort aimed at children from birth to the age of six which is carried out through the provision of educational stimuli. The family environment plays a very important role as the closest environment and the first madrasah for early childhood. The purpose of this study is to provide insight to parents in providing first Islamic education to early childhood in the family environment so that later children will become generations of noble character. This study uses library research, which is research whose object of study uses library data in the form of books or others with a qualitative approach. The results obtained from this study indicate that the family environment has an important role in educating and supervising the development of early childhood so that it is in accordance with Islamic education. Parents are not only material givers but parents will also be an example for children. Because early childhood will easily imitate the behavior of the people around them. The good or bad environment that the child lives in will also affect his behavior, character and morals in everyday life.